A study on OPG/RANK/RANKL axis in osteoporotic bile duct-ligated rats and the involvement of nitrergic and opioidergic systems - Amir Hossein Doustimotlagh; Ahmad Reza Dehpour; Shahroo Etemad-Moghadam; Mojgan Alaeddini; Sattar Ostadhadi; Abolfazl Golestani (Wolters Kluwer Medknow Publications, 2018)
Chronic liver disease (CLD) affects millions of people and its impact on bone loss has become a subject of interest. Nitric oxide and endogenous opioids are suggested to increase during cholestasis/cirrhosis and may impact bone resorption by different mechanisms. The receptor activator of nuclear factor-κB (RANK)/RANK-ligand (RANKL)/osteoprotegerin (OPG) signaling pathway regulates bone resorption, but its role in metabolic bone disease subsequent to CLD is unknown. We aimed to investigate the involvement of nitrergic and opioidergic systems in bone loss relative to the RANK/RANKL/OPG pathway, in bile duct-ligated (BDL) rats. Eighty BDL/sham-operated (SO) rats received injections of 3 mg/kg/day Nω-Nitro-L-arginine methyl ester ± naltrexone (10 mg/kg/day) or saline for 28 days. Plasma bone turnover markers, OPG, RANK, and RANKL along with mRNA expression levels of the latter three were assessed. Plasma bone turnover markers and OPG level increased, but RANKL decreased in the BDL group compared with their SO controls (both: P ≤ 0.05). Administration of naltrexone reduced bone turnover markers and OPG level while increased RANKL content in comparison to BDL rats (P ≤ 0.05). As compared to untreated BDL rats, nitric oxide inhibition showed no effect on bone turnover marker i.e. OPG, RANK, and RANKL levels. BDL significantly increased RANK mRNA, but had no significant effect on RANKL and OPG mRNA expression. The lack of association between plasma levels and quantitative gene expression of RANKL and OPG suggests an indirect function of these markers in BDL rats. Considering that opioid receptor blockage by naltrexone in BDL animals caused a significant decrease in OPG and an increase in RANKL plasma contents, it could be postulated that the opioidergic system may have a regulatory effect on these bone markers.